Pandangan Ekonomi Syariah terhadap Bisnis Multi Level Marketing pada PT K-Link Indonesia Cabang Makassar: Sharia Economic Perspective on Multi-Level Marketing Business at PT K-Link Indonesia, Makassar Branch - Masrahati, Masrahati; Iswandi, Heri; Fatmawati, Fatmawati; Fajrul, Muh (FAI UIM, 2023)
The rise of the Multi Level Marketing (MLM) business has made Islamic economists and business experts differ in their opinion in determining the laws of the business system. Based on this, this article will discuss the Islamic economic view of the MLM business system at PT K-Link Indonesia Makassar Branch. The method of this research is qualitative. The data of interview, documentation and field observations regarding the MLM business system at PT K-Link Indonesia Makassar Branch were then confronted with sharia economic theory so that syar'i laws could be established regarding the business. It was found that the work system of the Multi Level Marketing (MLM) business of PT K-Link Indonesia Makassar Branch in the view of sharia is in the muamalah category, which in principle is permissible based on the rules of fiqh. However, when there are elements that are prohibited in Islamic literature and found in MLM, this should not be done.